Genome-wide analysis of the homeodomain-leucine zipper family in Lotus japonicus and the overexpression of LjHDZ7 in Arabidopsis for salt tolerance - Wang, Dan; Gong, Yuan; Li, Yang; Nie, Shuming (Frontiers in Plant Science, 2022)
The homeodomain-leucine zipper (HD-Zip) family participates in plant growth, development, and stress responses. However, little information is known about the HD-Zip family in Lotus japonicus. Here, we identified 40 HD-Zip transcription factors of Lotus japonicus and divided them into four groups according to their phylogenetic relationships. The protein characteristics and gene structures of the HD-Zip family are complex and diverse, and each member may have different functions. Based on the stress-responsive cis-acting regulatory element of the promoter sequence, we selected six candidate genes of HD-Zip I. We further determined the expression pattern of these six genes in different organs and their response to abiotic stresses, including cold, heat, PEG and salinity, by qPCR analysis. We found that the expression of the Lj0g3v0072079.1 (LjHDZ7) gene was strongly induced by abiotic stress, especially salt stress. Subsequently, we overexpressed LjHDZ7 in Arabidopsis. The transgenic plants grew obviously better than Col-0 plants under salt stress. Furthermore, LjHDZ7 transgenic lines accumulated higher proline contents and showed lower electrolyte leakage and MDA contents than Col-0 plants under salt stress. The superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activities of the LjHDZ7 overexpression lines were significantly higher than those of the Col-0 plants under salt stress. Therefore, these results showed that overexpression of LjHDZ7 increased resistance to salt stress in transgenic Arabidopsis plants. These studies have provided a foundation for a more comprehensive understanding of Lotus japonicus HD-Zip family members and showed that certain genes of this family can be used as valuable tools for improving abiotic stresses.